Justify my thug : a novel - Clark, Wahida ([United States] : Cash Money Content, 2011)
Tasha and Trae try to overcome their troubles and make their marriage work, while Jaz is facing drama of her own.
Keywords: African American criminals -- Fiction; African American women -- Fiction